Revision of Apocharips Fergusson (Hymenoptera: Figitidae: Charipinae) with description of three new species from Colombia - Ferrer-Suay, Mar; Paretas-Martínez, Jordi; Pujade-Villar, Juli (Zootaxa, 2013)
The genus Apocharips is here revised. Three previously described species are considered as valid: Apocharips angelicae Pujade-Villar & Evenhuis, 2002, A. hansoni Menke, 1993, and A. trapezoidea (Hartig, 1841). Apocharips eleaphila (Sil-vestri, 1915) and A. peraperta (Silvestri, 1915) are synonymyzed with A. trapezoidea. Three new species are here de-scribed: Apocharips colombiana Ferrer-Suay & Pujade-Villar n. sp., Apocharips tamanii Paretas-Martínez & Pujade- Villar n. sp. and Apocharips tropicale Ferrer-Suay & Paretas-Martínez n. sp. A key to the six species included in Apocharips is given.